Alternative method for determining anaerobic threshold in rowers - Giovani Dos Santos Cunha; Rafael Reimann Baptista; Jerri Luiz Ribeiro; Alvaro Reischak de Oliveira (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n4p367 In rowing, the standard breathing that athletes are trained to use makes it difficult, or even impossible, to detect ventilatory limits, due to the coupling of the breath with the technical movement. For this reason, some authors have proposed determining the anaerobic threshold from the respiratory exchange ratio (RER), but there is not yet consensus on what value of RER should be used. The objective of this study was to test what value of RER corresponds to the anaerobic threshold and whether this value can be used as an independent parameter for determining the anaerobic threshold of rowers. The sample comprised 23 male rowers. They were submitted to a maximal cardiorespiratory test on a rowing ergometer with concurrent ergospirometry in order to determine VO2máx and the physiological variables corresponding to their anaerobic threshold. The anaerobic threshold was determined using the Dmax (maximal distance) method. The physiological variables were classified into maximum values and anaerobic threshold values. The maximal state of these rowers reached VO2 (58.2±4.4 ml.kg-1.min-1), lactate (8.2±2.1 mmol.L-1), power (384±54.3 W) and RER (1.26±0.1). At the anaerobic threshold they reached VO2 (46.9±7.5 ml.kg-1.min-1), lactate (4.6±1.3 mmol.L-1), power (300± 37.8 W) and RER (0.99±0.1). Conclusions - the RER can be used as an independent method for determining the anaerobic threshold of rowers, adopting a value of 0.99, however, RER should exhibit a non-linear increase above this figure.